Severiano di Gabala: un nuovo frammento greco - Kim, Sergey (Orientalia christiana periodica, 2017)
The article is dedicated to a Greek fragment from the homily of Severian of Gabala In illud: Christus est oriens (CPG 4235), which has been identified in the ps.-Athanasian florilegium De communi essentia (CPG 2240). A new edition of the fragment based on two manuscripts (Paris, BnF, gr. 1115 and Basel, Universitatsbibliothek, A.III.4) replaces the older edition published in PG 28, 64-65. The edition of the Greek fragment is faced by an Italian translation of the correspondent portion of the homily conserved in Old Georgian.